Time reduction effect of the enhanced TACT method for high-rise residential buildings - Lee, Donghoon; Kim, Dong-Sub; Kim, Gwang-Hee; Kim, Sunkuk (Journal of Civil Engineering and Management, 2016)
The finish work on high-rise residential buildings is performed simultaneously with mechanical and electrical construction work, which results in frequent work interference and delay. This significantly hinders efficient schedule management. Critical Path Method (CPM) is inefficient when applied to high-rise residential building projects in which work is repeatedly carried out for each floor. Line-of-Balance (LOB) is widely used for its effectiveness in managing repetitive work. LOB was developed into TACT and eTACT (enhanced-TACT) to combine heterogeneous works continuously. In particular, the eTACT schedule management method has an advantage in that it is capable of systematically connecting detailed construction, mechanical and electrical construction projects using a work planning template. This study evaluates the time reduction effect of the eTACT method for a high-rise residential building. A comparative analysis of data on 102 cases of non-applied projects and 44 cases of projects using the eTACT method over a period of 10 years is presented to verify its effectiveness. The result shows that finish work time was reduced by 25% or about 53 days on average.First published online: 18 Dec 2015